A series of new heteroleptic Hg(II) complexes: Synthesis, crystal structures and photophysical properties. (28th May 2016) - Mobin, Shaikh M.; Saini, Anoop Kumar; Mishra, Veenu; Chaudhary, Archana
Graphical abstract: Some new heteroleptic Hg(II) complexes were synthesized and characterized at ambient condition and their photo-physical properties were also investigated. Generation of a 1D polymeric chain via the amino group present at the meta position of carboxylic group have also been reported. This 1D polymeric chain exhibits interesting photo-physical properties with different emission spectra in different solvents. Abstract: We report the synthesis of six new heteroleptic Hg(II) complexes (1 –6 ) with general composition [Hg(II)(bpy)L2 ] where bpy = 2, 2′-bipyridine, L = benzoic acid (1 ), 2-amino benzoic acid (2 ), 3-amino benzoic acid (3 ), 4-amino benzoic acid (4 ), 2-hydroxy benzoic acid (5 ), 4-hydroxy benzoic acid (6 ).1, 2, 4 –6 are monomer with hexa coordinated Hg(II) center whereas3 is a zig – zag 1D-polymer with hepta-coordinated Hg(II) ion. Unlike other substituted benzoic acids, the 3-amino benzoic acid shows both –NH2 and –COOH groups having affinity towards Hg(II) centers. Therefore, on reaction of HgCl2 /HgBr2 with 3-amino benzoic acid it was observed that only –NH2 group coordinates to Hg(II) center and –COOH group remains uncoordinated yielding7 and8 .1 –6 have been characterized by elemental analysis, FT-IR, thermo gravimetric analysis as well as single crystal X-ray studies. Their photo-physical properties were also investigated and maximum quantum yield was observed for3 . Polymer3 exhibited different fluorescence spectra in different solvents with maximum emission in chloroform. The electronic communication and geometry optimization have been performed by Density Functional Theory.